Down's syndrome associated with two Robertsonian translocations, 45, XX, −15, −21, +t(15q21q) and 46, XX, −21, +t(21q21q). Issue 3 (September 1974) - Atkins, Leonard; Bartsocas, Christos S.
Abstract : A female infant with Down's syndrome was found to be a chromosomal mosaic with two cell lines in both blood and skin cells. One line carried a balanced 15/21 translocation, and the other line was effectively trisomic for chromosome 21 with a 21/21 translocation.